An assessment of the strategies that short term insurance companies can implement in order to improve the uptake of insurance products in Zimbabwe. - Mukayami, Moreblessing (2017)
Households and organisations in the world have come to accept that risk is inevitable in every sphere of life. The insurance mechanism has been used to address risks faced by both organisations and households. The purchase of insurance saw many people who have adopted it enjoy a number of benefits it brings. Like many African countries, Zimbabwe has also experienced low insurance penetration rate as a result of a number of challenges. The process of increasing the penetration rate has proven to be a rough walk with challenges which differ from one market to another. This study assessed the strategies that can be implemented in order to increase insurance uptake with particular reference given to the nonlife insurance industry of Zimbabwe. The study covered the period from December 2010 to December 2015. Simple random sampling was used in selecting 10 short term insurance companies out of the 20 registered with IPEC. Structured interviews and questionnaires were used as research instruments. The findings from the study were presented in graphs, charts and tables. Conclusions from the findings of the research showed that the currently implemented strategies are not adequate and hence there is high need for the adoption of strategies that are inclusive of the needs of the consumers. Furthermore, some insurance companies are failing to implement better strategies because of financial constraints. It has been recommended that the regulator be more flexible in regards to authorising the launch of new products and strategies and on the side of the insurance companies, it was recommended that they make products that enable consumers to get more coverage at lower costs since it has been noted that the insuring public has acute shortages of disposable income. Since consumer consumption patterns are changing, it was noted that there was high need for insurance companies to adapt to such changes through tailor making products as well as implementing a highly informative marketing strategy so as to enlighten consumers more about insurance concepts and products.